2013
DOI: 10.1007/s11605-013-2296-0
|View full text |Cite|
|
Sign up to set email alerts
|

Acute and Elective Laparoscopic Resection for Complicated Sigmoid Diverticulitis: Clinical and Histological Outcome

Abstract: Laparoscopic surgery for acute diverticular disease is safe and effective. Continuing bowl inflammations in histological specimens justify sigmoid resection in elective patients, but more effective pre-operative parameters need to be found to identify patients that would benefit from surgery during the initial episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 30 publications
4
19
0
1
Order By: Relevance
“…The stage of in ammation in diverticulitis surgery is the key for safe and successful surgery. Zdichavsky et al showed in 2013 that in histopathological examination of surgical specimen in early resected patients the stage of in ammation was more acute than in delayed cases [16]. Our intraoperative ndings con rmed this study in complicated diverticulitis disease.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The stage of in ammation in diverticulitis surgery is the key for safe and successful surgery. Zdichavsky et al showed in 2013 that in histopathological examination of surgical specimen in early resected patients the stage of in ammation was more acute than in delayed cases [16]. Our intraoperative ndings con rmed this study in complicated diverticulitis disease.…”
Section: Resultssupporting
confidence: 83%
“…Low number of patients, retrospective analyse are the main limitations of this study. An early operation approach is safe and showed a comparable morbidity in literature as well as in our study [16]. A detailed patient's history is required not to miss past episodes of diverticulitis.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…However, the cited paper by Zdichavsky et al [22] describes a semi-acute series after failed medical management of low grades of perforated diverticulitis. Although a slightly different population, these series do support the feasibility of laparoscopic sigmoidectomy in a contaminated abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Применительно к значению видеолапароскопической хирургической технологии в лечении ВОДБ, следует обратить внимание на итоги одноцентрового исследования Zdichavsky M. и соавт. [52], в рамках которого авторами были получены прекрасные результаты с низким числом осложнений: 14 % -при экстренных и 7 % -при плановых лапароскопических резекциях и отсутствием летальности. В исследовании Royds J. и соавт.…”
Section: плановая хирургия водбunclassified